Evaluation of the Properties of Encapsulated Stavudine Microparticulate Lipid-based Drug Delivery System in Immunocompromised Wistar Rats - Chime, Salome A.; Onunkwo, Godswill C.; Attama, Anthony A. (Current HIV Research, 2020)
Background: Lipid-based formulations have been confirmed to lower some side effects of drugs and can be tailor-made to offer sustained drug release of drugs with short half-life like stavudine. Aim: This study aimed to evaluate the immunomodulatory properties of stavudine-loaded solid lipid microparticles (SLMs) using immunocompromised Wistar rats. Methods: The SLMs were formulated by the homogenization method. The optimized batches were used for further in vivo studies. The effect of formulation on the CD4 count and the haematological properties of immunocompromised Wistar rats were studied. Results: The particle size range was 4 -8 μm, EE range was 85-93 % and maximum drug release was observed at 10 h. The CD4 cells increased from 115 ± 3.17 cell/mm3 at day zero to 495 ± 5.64 cell/mm3 at day 14 of treatment and 538 ± 6.31 cell/mm3 at day 21. The red blood cells increased from 2.64 ± 1.58 (x 106/mm3) at day zero to 6.96 ± 3.47 (x 106/mm3) at day 14 and 7.85 ± 3.64 (x 106/mm3) at day 21. PCV increased significantly (p < 0.05) to about 42-50 % at day 21 in the groups that received the SLMs formulations. White blood cells (WBC) also were 12 x 103/mm3, for SLM formulations, while the rats that received plain stavudine exhibited WBC of 9.6 x 103/mm3 at day 21. The histopathological studies revealed that oral stavudine-loaded SLMs had no significant damage to the kidney, liver, spleen and the brain of Wistar rats. Conclusion: The formulations exhibited significantly higher immunomodulatory properties than plain stavudine (p<0.05) and showed good properties for once daily oral administration and could be a better alternative to plain stavudine tablets for the management of patients living with HIV.
Keywords: CD4 cells